Can Judges Make Reliable Numeric Judgments? Distorted Damages and Skewed Sentences - Guthrie, Chris (2015)
In a series of studies involving over six hundred trial judges in three countries, we demonstrate that trial judges’ civil damage awards and criminal sentences are subject to influences that make them erratic. We found that the presence of misleading numeric reference points (or “anchors”) affected judges’ decisions in a series of hypothetical cases. Specifically, judges imposed shorter sentences when assigning sentences in months rather than in years; awarded higher amounts of compensatory damages when informed of a cap on damage awards; imposed different sentences depending upon the sequence in which criminal cases were presented to them; and were influenced by a plaintiff’s reference to a damage award seen on a “court TV show.” Taken together, the results suggest that unless judges take steps to reduce their susceptibility to anchors, their awards and sentences are apt to be highly unreliable. We also suggest how judges can safeguard against these influences and assign more stable awards and sentences